2016
DOI: 10.5376/ijms.2016.06.0024
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight Relationship, Condition Factor and Sex-ratio of Fish Fauna in Badagry Creek, Lagos, Nigeria.

Abstract: This study investigated the condition factor, growth pattern and sex ratio of fish species from Badagry creek, Lagos lagoon complex, Nigeria. A total of one thousand and eight specimens (1008) belonging to twelve (12) species were studied. The total length ranged from 12.85±1.54 -27.49±4.75cm, and body weight ranged from 38.50±14.04 -159.09±28.24g with Marcusenius senegalensis having the highest and Oreochromis niloticus having the least. All the fish species examined showed positive allometric growth (b > 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…This showed that more females were present than males and concur with the result of Kusemiju & Olaniya (1989) who reported a sex ratio of 1 male to 1.27 females in Lagos lagoon while Imevbore (1970) who obtained a sex ratio of 1 male to 1.40 females. This result was however in disagreement with the findings of Akintade et al (2016) who reported higher male populations of the silver catfish (C. nigrodigitatus) and for Tilapia melanotheron from Badagry creek, Lagos. Offem et al (2008) also reported similar findings from a water body in Cross River, Nigeria.…”
Section: Discussioncontrasting
confidence: 99%
“…This showed that more females were present than males and concur with the result of Kusemiju & Olaniya (1989) who reported a sex ratio of 1 male to 1.27 females in Lagos lagoon while Imevbore (1970) who obtained a sex ratio of 1 male to 1.40 females. This result was however in disagreement with the findings of Akintade et al (2016) who reported higher male populations of the silver catfish (C. nigrodigitatus) and for Tilapia melanotheron from Badagry creek, Lagos. Offem et al (2008) also reported similar findings from a water body in Cross River, Nigeria.…”
Section: Discussioncontrasting
confidence: 99%